Reciprocity as Deliberative Capacity: Lessons from a Citizen's Deliberation on Carbon Pricing Mechanisms in Australia. (June 2013) - Lo, Alex Y; Alexander, Kim S; Proctor, Wendy; Ryan, Anthony
Australia has seen a deep division in opinion in search of a carbon pricing mechanism. While concepts of carbon taxation and emission trading have comparable public support, climate scepticism is infuencing the debates in political and public spheres in downplaying the need for carbon pricing. Public deliberation is a possible engagement option to address the conflict inherent in climate policy preferences. This research explores the way that a deliberative forum involving twenty-four Australians promoted effective communication between participants through which conflict between policy preferences became more tangible. While the forum did not eliminate disagreement in preferences in the choice of carbon pricing mechanisms, participants reached consensus on fundamental principles such as the need for trusted sources of information, trusted governance procedures, and transparent accountability by appropriate institutions. Shared political expectations encouraged dialogue and cooperation in discussions by enhancing reciprocal understanding. Two sceptical participants who originally had strong opinions different from the rest of the group managed to find common ground. Public deliberative forums that are conducive to reciprocal communication are able to provide a mechanism for joint problem-solving processes that are less adversarial and more responsive to the range of people's preferences.